Method of Choice of Anesthesia for Circumcision in Preventing Penile Cancer - Perdana, I Gede Sukma Okta; Oki Lestari, Desak Putu (Journal of Comprehensive Science, 2025)
Circumcision is a common minor surgical procedure performed not only for cultural or religious reasons but also as a preventive measure against infectious diseases and penile cancer. The selection of an appropriate anesthesia method plays a critical role in ensuring patient comfort and procedural effectiveness. This study aims to examine the most suitable anesthesia techniques in circumcision procedures with a focus on their preventive role against penile cancer. The method employed is a systematic literature review of clinical and epidemiological journals discussing the link between circumcision, anesthesia techniques, and penile cancer incidence. The results indicate that local anesthesia, particularly the dorsal penile nerve block, is most recommended due to its efficiency, safety, and minimal postoperative pain. Circumcision is shown to reduce the risk of HPV infection and balanitis, two contributing factors to penile cancer. In conclusion, the appropriate choice of anesthesia in circumcision enhances patient experience and reinforces its role as a preventive measure against penile cancer.